Evaluation of Reid’s Combined Colposcopic Index as a predictor of cervical intraepithelial lesion - Verma, Indu; Pundhir, Pratibha; Kaur, Tejinder; Jain, Veena; Sood, Dinesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Carcinoma cervix is the commonest cancer among women worldwide and in India it accounts for 80% of all genital cancers. Screening methods include cervical cytology, human papilloma virus testing and colposcopy. Objective of present study was to evaluate suspicious cervix colposcopically using Reids Colposcopic Index (RCI) and to correlate RCI with histopathological findings. Methods: This was a prospective cross sectional study done on 125 women with clinical diagnosis of suspicious cervix. Colposcopy was performed and grading of the disease was done according to RCI. Positive cases were subjected to cervical biopsy and endocervical curettage was performed in unsatisfactory colposcopy. Results: Colposcopy was done on 125 women with suspicious cervix. Out of 125, sixty two showed abnormal colposcopic findings which were graded according to RCI into Low grade disease predicting histological diagnosis of CIN1 in 47, Intermediate grade disease predicting histological diagnosis of CIN1/2 in 11 and High grade disease predicting histological diagnosis of CIN2/3 in 4 women. Colposcopy of one women suggested invasive carcinoma and was confirmed on histopathology to be microinvasive squamous cell carcinoma. Six women with unsatisfactory colposcopy showed benign histopathology. Sensitivity, specificity, predictive value and false negative rate of colposcopy for invasive disease was 50%, 100%, 100% and 1.60% respectively with 98.40% diagnostic accuracy. Colposcopic diagnosis of invasive disease and histopathology report showed 100% correlation. Conclusions: Correlation between RCI and histopathology was good. Predictive accuracy of colposcopy increased with increasing severity of disease.